Local Community and Tourism Development: A Study of Rural Mountainous Destinations - Jaafar, Mastura; Mohd Bakri, Norjanah; Rasoolimanesh, Mostafa (Canadian Center of Science and Education, 2015)
Malaysia is internationally regarded as a popular rural destination because of its natural heritage. Rural tourism is increasingly viewed as a panacea for increasing the economic viability of marginalized areas, stimulating social regeneration, and improving the living conditions of rural communities. This study explores local community involvement in a rural tourism development in Kinabalu National Park, Sabah. We explore how the local community perceives their involvement in a local rural tourism development and look to identify the benefit of tourism destination development for this community. To address these objectives, we employed quantitative research methodologies and a sample of 378 respondents drawn from villages surrounding Kinabalu National Park. Sampled residents indicated having positive perceptions of tourism development in the area. Local communities enjoy being involved in the tourism sector because it improves their key income resources and quality of life.